Real-time monitoring of calcium carbonate and cationic peptide deposition on carboxylate-SAM using a microfluidic SAW biosensor - Pohl, Anna; Weiss, Ingrid M. (Beilstein Journal of Nanotechnology, 2014)
A microfluidic biosensor with surface acoustic wave technology was used in this study to monitor the interaction of calcium carbonate with standard carboxylate self-assembled monolayer sensor chips. Different fluids, with and without biomolecular components, were investigated. The pH-dependent surface interactions of two bio-inspired cationic peptides, AS8 and ES9, which are similar to an extracellular domain of the chitin synthase involved in mollusc shell formation, were also investigated in a biological buffer system. A range of experimental conditions are described that are suitable to study non-covalent molecular interactions in the presence of ionic substances, such as, mineral precursors below the solubility equilibrium. The peptide ES9, equal to the mollusc chitin synthase epitope, is less sensitive to changes in pH than its counterpart AS8 with a penta-lysine core, which lacks the flanking acidic residues. This study demonstrates the extraordinary potential of microfluidic surface acoustic wave biosensors to significantly expand our experimental capabilities for studying the principles underlying biomineralization in vitro.
Keywords: biomineralization; calcium carbonate; love-type surface acoustic wave; poly-cationic peptide

On Biomineralization - Lowenstam, H. A.; Weiner, S. (Oxford Univ. Press, 1989)

(untitled) - Weiner, S.; Addadi, L. (Annu. Rev. Mater. Res., 2011)

(untitled) - Addadi, L.; Vidavsky, N.; Weiner, S. (Z. Kristallogr. – Cryst. Mater., 2012)

Molecular Biology of the Cell: Reference Edition - Alberts, B.; Johnson, A.; Lewis, J.; Raff, M.; Roberts, K.; Walter, P. (Garland Science, 2007)

Biomineralization: Principles and Concepts in Bioinorganic Materials Chemistry - Mann, S. (Oxford University Press, 2001)

(untitled) - Knoll, A. H. (Rev. Mineral. Geochem., 2003)

(untitled) - Raven, J. A.; Knoll, A. H. (Geomicrobiol. J., 2010)

(untitled) - Gao, H.; Ji, B.; Jäger, I. L.; Arzt, E.; Fratzl, P. (Proc. Natl. Acad. Sci. U. S. A., 2003)

Met. Ions Life Sci. - Biomineralization: From Nature to Application - Weiss, I. M.; Marin, F. (John Wiley & Sons, 2008)

(untitled) - Meldrum, F. C.; Cölfen, H. (Nanoscale, 2010)

(untitled) - Addadi, L.; Joester, D.; Nudelman, F.; Weiner, S. (Chem. – Eur. J., 2006)

Engineering of Crystalline Materials Properties State of the Art in Modeling, Design and Applications - Addadi, L.; Politi, Y.; Nudelman, F.; Weiner, S. (Biomineralization design strategies and mechanisms of mineral formation: operating at the edge of instability, 2008)

(untitled) - Falini, G.; Albeck, S.; Weiner, S.; Addadi, L. (Science, 1996)

(untitled) - Suzuki, M.; Iwashima, A.; Kimura, M.; Kogure, T.; Nagasawa, H. (Mar. Biotechnol., 2013)

(untitled) - Marin, F.; Le Roy, N.; Marie, B. (Front. Biosci., Scholar Ed., 2012)

(untitled) - Marie, B.; Joubert, C.; Tayalé, A.; Zanella-Cleón, I.; Belliard, C.; Piquemal, D.; Cochennec-Laureau, N.; Marin, F.; Gueguen, Y.; Montagnani, C. (Proc. Natl. Acad. Sci. U. S. A., 2012)

(untitled) - Marie, B.; Ramos-Silva, P.; Marin, F.; Marie, A. (Proteomics, 2013)

(untitled) - Levi-Kalisman, Y.; Falini, G.; Addadi, L.; Weiner, S. (J. Struct. Biol., 2001)

(untitled) - Miyamoto, H.; Endo, H.; Hashimoto, N.; Limura, K.; Isowa, Y.; Kinoshita, S.; Kotaki, T.; Masaoka, T.; Miki, T.; Nakayama, S.; Nogawa, C.; Notazawa, A.; et al. (Zool. Sci., 2013)

(untitled) - Weiss, I. M. (Z. Kristallogr. – Cryst. Mater., 2012)

(untitled) - Meldrum, F. C.; Cölfen, H. (Chem. Rev., 2008)

(untitled) - Yang, X.; Xie, B.; Wang, L.; Qin, Y.; Henneman, Z. J.; Nancollas, G. H. (CrystEngComm, 2011)

(untitled) - Borah, B. M.; Halter, T. J.; Xie, B.; Henneman, Z. J.; Siudzinski, T. R.; Harris, S.; Elliott, M.; Nancollas, G. H. (J. Colloid Interface Sci., 2014)

(untitled) - Nielsen, M. H.; Li, D.; Zhang, H.; Aloni, S.; Han, T. Y.-J.; Frandsen, C.; Seto, J.; Banfield, J. F.; Cölfen, H.; De Yoreo, J. J. (Microsc. Microanal., 2014)

Research Methods in Biomineralization Science - De Yoreo, J. J. (Academic Press, 2013)

Intermolecular and Surface Forces - Israelachvili, J. N. (Academic Press, 2011)

(untitled) - Gebauer, D.; Kellermeier, M.; Gale, J. D.; Bergström, L.; Cölfen, H. (Chem. Soc. Rev., 2014)

(untitled) - Verch, A.; Gebauer, D.; Antonietti, M.; Cölfen, H. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Perpeet, M.; Glass, S.; Gronewold, T.; Kiwitz, A.; Malavé, A.; Stoyanov, I.; Tewes, M.; Quandt, E. (Anal. Lett., 2006)

Advances in Surface Acoustic Wave Technology, Systems and Applications - Ruppel, C. C. W.; Fjeldly, T. A. (World Scientific Publishing Co. Pte. Ltd., 2001)

(untitled) - Jung, A.; Gronewold, T. M. A.; Tewes, M.; Quandt, E.; Berlin, P. (Sens. Actuators, B, 2007)

(untitled) - Hoummady, M.; Campitelli, A.; Wlodarski, W. (Smart Mater. Struct., 1997)

Thin Film Materials: Stress, Defect Formation and Surface Evolution - Freund, L. B.; Suresh, S. (Cambridge University Press, 2009)

(untitled) - Andle, J. C.; Vetelino, J. F. (Sens. Actuators, A, 1994)

(untitled) - Gronewold, T. M. A. (Anal. Chim. Acta, 2007)

(untitled) - Cui, J.; Iturri, J.; Götz, U.; Jimenez, M.; del Campo, A. (Langmuir, 2013)

(untitled) - Länge, K.; Rapp, B. E.; Rapp, M. (Anal. Bioanal. Chem., 2008)

(untitled) - Joseph, S.; Gronewold, T. M. A.; Schlensog, M. D.; Olbrich, C.; Quandt, E.; Famulok, M.; Schirner, M. (Biosens. Bioelectron., 2005)

(untitled) - Kellermeier, M.; Cölfen, H.; Gebauer, D. (Methods Enzymol., 2013)

(untitled) - Weiss, I. M.; Kaufmann, S.; Mann, K.; Fritz, M. (Biochem. Biophys. Res. Commun., 2000)

(untitled) - Weber, E.; Guth, C.; Weiss, I. M. (PLoS One, 2012)

(untitled) - Weber, E.; Bloch, L.; Guth, C.; Fitch, A. N.; Weiss, I. M.; Pokroy, B. (Chem. Mater., 2014)

(untitled) - Gotliv, B.-A.; Addadi, L.; Weiner, S. (ChemBioChem, 2003)

(untitled) - Pokroy, B.; Aizenberg, J. (CrystEngComm, 2007)

(untitled) - Pokroy, B.; Chernow, V. F.; Aizenberg, J. (Langmuir, 2009)

(untitled) - Sengupta Ghatak, A.; Koch, M.; Guth, C.; Weiss, I. M. (Int. J. Mol. Sci., 2013)

(untitled) - Weiss, I. M.; Schönitzer, V.; Eichner, N.; Sumper, M. (FEBS Lett., 2006)

(untitled) - Weiss, I. M.; Lüke, F.; Eichner, N.; Guth, C.; Clausen-Schaumann, H. (J. Struct. Biol., 2013)

Ger. Pat. Appl. - Tewes, M.; Glaß, S.; Schlensog, M. D.; Quandt, E. (Mass determination method for measuring the mass acting on a surface acoustic wave sensor, e.g., for use in micro-weighing scales, whereby a calibration is first carried out using an analyte, 2005)